The evaluation of implementation impact of centralized traffic control systems in railways - Magyla, Tomas (Transport, 2002)
In this article we propose to evaluate the utility of implementation of Centralized Traffic Control System EbiScreen using expert evaluations in indistinct numbers, in the form of trapezoid membership function, as we are confident in the advantages obtained using this evaluation method. The methodology of evaluating and weightng of criteria in a trapezoid membership form is proposed in this article together with the results of evaluation. The idea is to integrate the hierarchy of objectives with the multi-attribute weight vectors using the values obtained by the expert group in evaluation process. The additional weights for the attributes in the multi-attribute analysis are provided within the same scale, so that they can be combined to find the overall value of the evaluation. Methodological presentation is followed by the results of sample application in Lithuanian Railways where the object of evaluation was the EbiScreen Centralized Traffic Control System. First Published Online: 19 Dec 2011